Skill-Building Strategies Complex Problem Solving For Generation Z - Ismail, Dingot Hamonangan; Nugroho, Joko; Akbar , Muhammad Yusuf; Hanifah, Dhiya Aulia (Yayasan Sinergi Kawula Muda, 2024)
In the ever-evolving digital era, complex problem-solving skills are essential for Generation Z to adapt and compete in the global job market. This article discusses various practical strategies that can be used to develop these skills, focusing on innovative approaches to education and training. This study uses a literature study of Sinta-accredited journal articles and reputable international journals. The results of the study show that several things need to be done in the process of developing complex problem-solving soft skills, namely, Attention to the uniqueness of Gen Z, The use of best practices from the latest approach through learning, and the use of technology in the development of complex problem-solving. The implications of this research on science are that it enriches the educational literature by providing practical guidance on effective strategies to develop complex problem-solving skills in Generation Z, improving the quality of education, the use of technology in education and the identification of best practices from the latest approaches to developing complex problem-solving skills that Gen Z needs to adapt and compete in the era of the Industrial revolution.